Assessment Of Genetic Diversity Among Chickpea (Cicer Arietinum L.) Genotypes Using Seed Storage Protein Profiling And Rapd Markers (Applied Biological Research, 2017)
Seed storage protein profiling and RAPD were used in present study for the  analysis of genetic diversity among 15 chickpea genotypes. SDS-PAGE of seed  storage protein differentiated 15 genotypes into three major clusters. RAPD  analysis was done using highly polymorphic ten primers which amplified 104  bands with 2.70 average polymorphic bands. RAPD analysis reported 24.4  average per cent polymorphism and highest in OPH-03. OPH-19 reported  highly informative primer based on PIC and MI value. Similarity coefficients  of RAPD data were ranged from 0.55 to 0.95. Dendrogram generated three  major clusters which distinguished Fusarium wilt susceptible and resistant  genotypes in cluster I and cluster II, respectively, whereas cluster III included both resistant and susceptible genotypes. RAPD marker was found more  informative than seed storage protein profiling for diversity analysis. Further,  no specific banding was detected that could discriminate resistant from  susceptible genotypes critically.
Keywords: Cicer arietinum; Fusarium wilt; genetic diversity; RAPD; SDS; PAGE; seed storage protein